Individual factors on readiness of youth fishermen in Malaysia to use Global Positioning Systems - Omar, Siti Zobidah; Osman, Mohd Nizam; Bolong, Jusang; Alby, Jeffrey Lawrence D'Silva; Mohamed Shaffril, Hayrol Azril (Asian Network for Scientific Information, 2014)
The main aim of this study is to identify the individual factors that might impinge young (aged between 15-40 years old) fishermen’s readiness to use Global Positioning Systems (GPS) at sea. The study was quantitative in nature and via a multi-stage simple-random sampling, a total of 240 young fishermen from four selected fishing districts have been selected as the respondents. In general, the young fishermen were moderately ready to use the GPS at sea. The inferential analyses performed have confirmed that the factors of education level and catchment area have recorded significant difference with readiness for GPS usage while factors of age and number of crew members have recorded a positive and significant relationship with readiness for GPS usage. A number of recommendations have been discussed and it is hoped that such recommendations will assist the relevant parties in developing strategies to enhance usage of fishing technologies among fishermen in Malaysia-particularly the younger ones.